ANALISIS KUALITAS PELAYANAN, CITRA MEREK, DAN ONGKOS KIRIM TERHADAP KEPUASAN PELANGGAN DI J&T CARGO KEDIRI - Salma, Vivi (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the effect of service quality, brand image, and shipping costs on customer satisfaction at PT. Global Jet Express Cargo (J&T Cargo) Kediri. The research employed a quantitative approach using a survey method. The study population consisted of customers who used J&T Cargo services during September–December 2024, with 100 respondents selected through purposive sampling. Data were collected using structured questionnaires and analyzed using multiple linear regression, classical assumption tests, simultaneous tests (F-test), partial tests (t-test), and coefficient of determination (R²). The results show that service quality and shipping costs have a significant positive effect on customer satisfaction, while brand image does not have a significant effect. Simultaneously, service quality, brand image, and shipping costs significantly influence customer satisfaction. The coefficient of determination indicates that most variations in customer satisfaction can be explained by the examined variables. These findings highlight the importance of improving service performance and pricing strategies to enhance customer satisfaction in the cargo delivery service sector.